Protective effects of resveratrol in high fat diet– and metals (Al, Pb, As)-induced metabolic and cognitive impairments (Bangladesh Journal of Pharmacology, 2025)
This study evaluated the neuroprotective role of resveratrol in rats co-exposed to high fat diet and metals (aluminum, lead, arsenic) for 60 days. Rats (male, 10–12 weeks age, 180–250 g) were divided into control, modified meal (high fat diet + metals in drinking water), and resveratrol-treated groups (5 and 20 mg/kg). Behavioral tests (Morris water maze, Y maze, social interaction) revealed impairments in memory and reduced sociability in the modified meal group. Biochemical and histological analyses showed dysregulated lipid profiles, elevated blood glucose, signs of liver and kidney dysfunction, neuronal loss, and structural damage in the hippocampus. Resveratrol treatment, particularly at 20 mg/kg, significantly restored cognitive performances by increasing time spent in the target quadrant (78.9 ± 2.0; p